Reversal of acetaminophen-generated oxidative stress and concomitant hepatotoxicity by a phytopharmaceutical product - Afolabi C. Akinmoladun; Kehinde O. Oguntunde; Lawrence O. Owolabi; Omotayo B. Ilesanmi; Joan O. Ogundele; M.Tolulope Olaleye; Afolabi A. Akindahunsi (Food Science and Human Wellness)
The increasing popularity of herbal medicine and the well-established health benefits of phytochemicals have spurred the multiplicity of nutraceutical and phytopharmaceutical products. In this study, Trévo™, a nutraceutical and phytopharmaceutical product, was evaluated for beneficial effects in acetaminophen-induced hepatic toxicity in Wistar rats. Animals received Trévo™ (1.5 mL/kg, 3.0 mL/kg or 4.5 mL/kg) orally for 14 days. Hepatotoxicity was induced by the oral administration of acetaminophen (2 g/kg), 24 h prior to sacrifice. Biochemical liver function tests, oxidative stress indicators and histoarchitectural changes were evaluated. Acetaminophen administration occasioned significant increase (P < 0.05) in serum bilirubin level and activities of the aminotransferases, alkaline phosphatase, γ-glutamyltransferase and lactate dehydrogenase accompanied by a significant decrease (P < 0.05) in albumin level as well as histopathological alterations in liver sections. Promotion of hepatic oxidative stress by acetaminophen was revealed by significant (P < 0.05) increase in lipid peroxidation, depletion of reduced glutathione, and decrease in superoxide dismutase and catalase activities. Administration of Trévo™ remarkably ameliorated acetaminophen-induced histopathological alterations and changes in serum and tissue biochemical markers. The protective effect of Trévo™ (4.5 mL/kg) was at par with that of Silymarin (25 mg/kg). The present study indicates that Trévo™ has notable salubrious effects.